South America (Patagonia [Argentina and Chile]) - The Nature Conservancy (Symphony in the Flint Hills, 2015)
An introduction to the Patagoninan Grasslands in South America. Stretching from the foothills of the Andes in Chile to the Atlantic coast of Argentina, the Patagonian grasslands are a reminder of untamed wilderness and wide-open plains. The region is home to the legendary gauchos, Argentine cowboys known for their skill with horses and their penchant for mate, a brew of stimulating South American herbs served in hollowed-out gourds.
Keywords: grasslands; plains; nature; natural; grass; countries; South America; wilderness; animals; resources; Plant species